Effects of the dopamine D3 receptor agonist 7‐hydroxy‐2‐(di‐N‐propylamino) tetralin in hyperthyroidism‐induced premature ejaculation rat model. (25th January 2018) - Cinar, O.; Durmus, N.; Aslan, G.; Demir, O.; Evcim, A. S.; Gidener, S.; Esen, A. A.
Summary: Various factors are involved in the aetiology of premature ejaculation (PE). Hyperthyroidism is one of the causes of acquired PE, but the exact mechanism by which it causes the disorder is not yet understood. The aim of this study was to evaluate the role of the dopaminergic system in hyperthyroidism‐induced PE by the intracerebroventricular microinjection of the preferentially active dopamine receptor agonist 7‐hydroxy‐2‐(di‐ N ‐propylamino) tetralin (7‐OH‐DPAT) in a rat model of this disorder. Wistar rats were randomly divided into hyperthyroid and control groups, and ejaculation was induced by the ICV administration of 7‐OH‐DPAT. To evaluate the emission and expulsion phases of ejaculation, measurements of seminal vesicle pressure (SVP) and electromyographic recordings of the bulbospongiosus muscle were taken. The interval between the 7‐OH‐DPAT administration and the first ejaculation was significantly less in the hyperthyroid group ( p  <   .01) than in the control group, and the maximum amplitude of the SVP values revealed a statistically significant difference between the groups ( p  <   .01). The intervals between contractions of the seminal vesicle and bulbospongiosus muscles were also significantly less in the hyperthyroid group ( p  =   .0187) than in the control group. No other results differed significantly between the groups. This study determined that hyperthyroidism altered only the emission phase of ejaculation.